Gambaran Karakteristik Individu Penderita Dermatofitosis Di Poli Kilinik Penyakit Kulit Dan Kelamin Rsud Dr. Soedarso Pontianak - Cau Kim Jiu; Wuriani Wuriani; Veronika Mansunomi (Jurnal Keperawatan dan Kesehatan, 2015)
Background: Diseases caused by dermatophyte fungi group called "Dermatophytosis". Aims: The purpose of this study is to describe characteristics of individuals with dermatophytosis in Polyclinic Dermatology and Venereology Dr. Soedarso’s Hospital Pontianak. Methods: The samples in this study were 54 patients with a diagnosis of dermatophytosis. The independent variable in this study is composed of age, sex, occupation, education, socio economic status, marital status and personal hygiene. Results: Based on the results of the univariate analysis found that the characteristic age is the age category of respondents with elderly, gender characteristics of the respondents are male sex, characteristics of education is the education level of the respondents graduated from college, job characteristics is respondent with a job house wife, characteristics of marital status is the status of married respondents, characteristics of the social status of the respondents with higher socio economic status, and characteristics of personal hygiene are respondent already doing personal hygiene behaviors that are good enough. Conclusions: Effort do to prevent fungal skin infectionis to maintain the effectiveness of the practice of personal hygiene routineis by using soap bath at least twice a day, change clothes and hygiene items whose usein contact with skin.